Clypeina tibanai, sp. nov. (Polyphysacea, Dasycladales, Chlorophyta), mid-cretaceous green alga from the Potiguar Basin, Brazilian margin of the young South Atlantic Ocean - Granier, B.; Dias-Brito, D. [UNESP]; Bucur, I. I. (Edicions de la Universitat de Barcelona, 2014)
The fossil genus Clypeina (Michelin, 1845) comprises some 40 species. We describe Clypeina tibanai, a new species from? upper Albian-Cenomanian strata of the Potiguar Basin, Brazil, characterised by closely set verticils of tubular, bended laterals. It is compared with Clypeina hanabataensis Yabe & Toyama, 1949, a Late Jurassic species, and with Pseudoactinoporella fragilis (Conrad, 1970), an Early Cretaceous taxon. The new species belongs to a short list of green algae found in the young South Atlantic oceanic corridor, an assemblage defining a phycological paleobioprovince discrete from that of the Tethyan realm.
Keywords: Albian; Cenomanian; Cladosporate; Clypeina; Cretaceous; Dasycladales; Polyphysaceae